Modeling Human Heart Blood Circulation Using Hexa Graph Topology - T.Kalaiselvi; M.Nandhini; K.Menakapriya; G.Sindhu; M.Gowri Manohari; S.Santhiya (Utilitas Mathematica, 2025)
the concept of heart blood circulation through specific topologies the Right Hexa Graph Topology and the Left Hexa Graph Topology provides an innovative and structured approach to represent the connectivity and flow of blood within the human heart. These topological models abstractly capture the physiological pathways while maintaining the essential features of the circulatory system. In this paper, the human heart’s anatomy is modeled as a directed graph, where vertices correspond to key anatomical structures such as the superior vena cava, right atrium, tricuspid valve, pulmonary veins, left atrium, mitral valve, and others, and edges represent the directional flow of blood between them. Two distinct hexa graph frameworks are developed: one for deoxygenated blood flow from the body to the lungs (Right Hexa Graph Topology), and another for oxygenated blood flow from the lungs to the body (Left Hexa Graph Topology). For each pathway, the lower hexa subgraphs, upper hexa subgraphs, and boundary hexa subgraphs are explicitly constructed. The resulting topologies offer a systematic framework to visualize, understand, and analyze the dynamic blood circulation process, emphasizing critical transitions and structural interconnections in the human heart.